CEMACS USM TO ENHANCE RESEARCH AND TECHNOLOGY TRANSFER WITH VARIOUS AGENCIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, September 2015 – Universiti Sains Malaysia (USM) plans to establish partnerships with various research centres and worldrenowned academicians to further strengthen the field of biodiversity studies through research collaborations and technology transfer.